Antioxidant Activity and Phenolics of Kabau (Archidendron bubalinum) Pod Peel Extract from East Lampung on Blood Cell Male Mice Induced by Cadmium - Elisa Nurma Riana; Muhammad Eka Prastya; Gian Primahana; Hida Arliani Nur Anisa; Iffa Afiqa Khairani; Lisana Husna Imaniar (Institut Pertanian Bogor, 2025)
Cadmium (Cd) increases oxidative stress, which increases the likelihood of health problems. To protect the body from oxidative stress, natural antioxidants obtained from plants are required. The kabau plant (Archidendron bubalinum) is thought to have antioxidant phytochemicals. The purpose of this study was to assess the antioxidant activity and total phenolic component content of kabau pod peels, as well as their effect on the quantity of erythrocytes and leukocytes in male mice exposed to cadmium. This study used a completely randomized design, with 24 mice divided into six groups: three control groups and three treatment groups. The findings of assessing the antioxidant activity of peel extract revealed that the IC50 was 93.6 ppm, which is considered strong. The phenolic content of peel extract was 72.26 mg GAE/g. Giving pod peel extract to mice increased the number of erythrocytes and leukocytes, however the impact was not significant (p = 0.028 and P = 0.239). Mice with 380 mg/kg BW produced better outcomes. Keywords: antioxidant, Archidendron, blood cell, kabau, phenolics